Synergic effect of dielectric barrier discharge plasma and hydrodynamic cavitation on decolorization of methylene blue - Ahmad Ahadi; Amirhossein Zali; Mohammad Ghorbanalilu; Hamid Ghomi (PLoS ONE, 2026)
The growing demand for efficient and sustainable wastewater treatment technologies has driven the development of advanced oxidation processes (AOPs) that combine multiple physical and chemical mechanisms. In this study, we introduce a novel hybrid system that integrates Dielectric Barrier Discharge (DBD) plasma with Hydrodynamic Cavitation (HDC) to achieve rapid decolorization of Methylene Blue (MB) in both distilled and tap water. Experimental conditions included applied AC voltages ranging from 7 to 12 kV and initial MB concentrations of 10–40 mg/L, with samples collected over treatment times up to 15 minutes. Complete decolorization was consistently achieved within 15 minutes, with ~80% removal typically occurring in less than 5 minutes. Notably, the energy utilization efficiency for the most concentrated solution (40 mg/L) at full decolorization reached 4.6 g/kWh, surpassing previously reported values (<4 g/kWh). Direct plasma–cavitation coupling (direct DBD-HDC mode) outperformed the indirect configuration, highlighting the synergistic effects of simultaneous microbubble cavitation and plasma-generated reactive oxygen species (ROS). Optical Emission Spectroscopy (OES) confirmed the presence of key oxidants such as hydroxyl radicals (•OH), which play a dominant role in dye degradation. These findings establish DBD-HDC hybridization as a powerful and energy-efficient AOP, with strong potential for scalable application in wastewater treatment and other environmental remediation processes.